Budaya Kepenjaraan Narapidana Terorisme High Risk di Lapas Kelas IIA Pasir Putih Nusa Kambangan - Shana Lia Mifroh; Vinita Susanti (Universitas Batanghari Jambi, 2026)
The prison culture at Pasir Putih Class IIA Correctional Facility reflects distinctive approaches to management, programs, and daily activities compared to other correctional institutions. Through its high-security regime, the facility restricts inmates’ activities in order to control their movement and prevent undesirable interactions, thereby minimizing the potential formation of new criminal networks. Pasir Putih Class IIA Correctional Facility also plays a strategic role in the rehabilitation of high-risk inmates by suppressing the spread of radical ideology while facilitating processes of rehabilitation and social reintegration, enabling them to return as productive and peaceful members of society.